Postseismic deformation model of the 2024 Noto Peninsula earthquake, central Japan - Hisashi Suito (Earth, Planets and Space)
Abstract We investigated the characteristics and mechanism of postseismic deformation following the 2024 Noto Peninsula earthquake (M7.6), which occurred on January 1, 2024, in the Noto Peninsula, Japan. The observed postseismic deformation for 10 months after the earthquake indicated that the magnitude of the horizontal deformation near the fault (Noto Peninsula) and farther away (Niigata Prefecture and Toyama Prefecture) was nearly the same, ranging from 2 to 4 cm toward the northwest. Regarding vertical deformation, subsidence of several centimeters was observed in the Noto Peninsula, while uplift of a few centimeters was observed from Niigata Prefecture to Toyama Prefecture. No single mechanism, poroelastic rebound, afterslip, or viscoelastic relaxation, could explain all the observed deformations. The key to understanding multiple mechanisms lied in the vertical deformation particularly, the deformation at the Hegura Island station, the only station located northwest of the focal region. Based on the constraint that the Hegura Island station subsides, we constrained the parameters governing viscoelastic relaxation and then estimated afterslip based on the data that removed the deformation caused by viscoelastic relaxation. This approach allowed us to explain the observed horizontal and vertical deformations. The estimated optimal thickness of the elastic layer and viscosity were 40 km and 4 × 1018 Pa·s, respectively. Afterslip was estimated in the northern part of the Noto Peninsula. The postseismic deformation for 10 months after the earthquake was dominated by viscoelastic relaxation, and the effects of the afterslip were confined to the northern part of the Noto Peninsula. The slip distribution differed significantly when considering only afterslip compared to when considering multiple mechanisms. Focusing on a single mechanism can lead to misinterpretations. Finally, since postseismic deformation of several mm/yr is expected to continue for decades or longer, it must be remembered that postseismic deformation is included in the monitoring of crustal deformation in this region. Graphical Abstract